2019
DOI: 10.1002/adhm.201801511
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Nanoparticles Restore Lysosomal pH and Autophagic Flux in Lipotoxic Pancreatic Beta Cells

Abstract: between autophagosome and a sufficiently acidic lysosome (Figure 1). In the insulin secreting pancreatic beta cells (β-cells), chronic exposure to high levels of fatty acids results in lipotoxicity [7,8] and leads to disruption of autophagy concomitant with compromised lysosomal acidity. This autophagic dysfunction affords an increased accumulation of damaged organelles and proteins in the cells, thereby exacerbating the decline in cellular functions which leads to progressive diseases such as Type II diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 30 publications
(47 reference statements)
0
36
0
Order By: Relevance
“…The mechanism by which LAL overexpression alters autophagy remains to be elucidated. Previous studies have shown that rescuing lysosomal pH, which was increased with steatosis, restored autophagy flux 48 . This leads us to question whether therapies aimed at restoring lysosomal pH may be more viable than enhancing LAL abundance or activity.…”
Section: Discussionmentioning
confidence: 93%
“…The mechanism by which LAL overexpression alters autophagy remains to be elucidated. Previous studies have shown that rescuing lysosomal pH, which was increased with steatosis, restored autophagy flux 48 . This leads us to question whether therapies aimed at restoring lysosomal pH may be more viable than enhancing LAL abundance or activity.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, intermittent fasting did not improve β cell survival or regeneration in lysosomal associated membrane protein-2 (Lamp2) knockout mice, again suggesting a central role of lysosome function in β cell homeostasis. In line with this notion, recent studies have proposed to improve lysosomal function in the β cell by using bioengineered nanoparticles designed to lower lysosomal pH [96,97].…”
Section: Stimulating β Cell Macroautophagy: Potential Therapies In DImentioning
confidence: 98%
“…Most endocytosed nanoparticles are transported to the lysosomes for elimination. Not only biodegradable polymers such as poly(D,L-lactide-co-glycolide) nanoparticles, but also metal oxide nanoparticles such as iron oxide nanoparticles can be degraded [39] , [40] , [41] , [42] . Therefore, strategies for escaping from the lysosomes were preferred for intracellular release of drugs, especially for gene drugs [43] , [44] , [45] .…”
Section: Resultsmentioning
confidence: 99%